2009
DOI: 10.1590/s0034-72802009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic cyclophotocoagulation in refractory glaucomas: a long term study

Abstract: Purpose: To evaluate the safety and efficacy of endoscopic cyclophotocoagulation (ECP) in the treatment of refractory glaucomas. Methods: The preoperative and postoperative courses of 539 eyes of 539 patients with refractory glaucoma who underwent ECP and had a minimum 5 years follow-up were retrospectively reviewed. All procedures were performed by a single surgeon (FEL). Eyes that were included had undergone at least one incisional glaucoma surgery and had intraocular pressure (IOP) equal to or above 35 mmHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 11 publications
0
29
1
Order By: Relevance
“…In advanced secondary glaucoma, the IOP reduction ranged from 26% to 68% (7 to 28 mmHg) or yielded a mean IOP decrease of 50% (18 mmHg) [ 70 , 71 , 74 76 ]. In the largest retrospective study on ECP (7.4 years of follow-up), Lima et al reported a postoperative IOP ranging between 6 and 21 mmHg in 79% of patients, with a mean number of medications of 1.9 [ 75 ].…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
“…In advanced secondary glaucoma, the IOP reduction ranged from 26% to 68% (7 to 28 mmHg) or yielded a mean IOP decrease of 50% (18 mmHg) [ 70 , 71 , 74 76 ]. In the largest retrospective study on ECP (7.4 years of follow-up), Lima et al reported a postoperative IOP ranging between 6 and 21 mmHg in 79% of patients, with a mean number of medications of 1.9 [ 75 ].…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
“…Finally, congenital glaucoma has been noted in a retrospective study to have a high failure rate of 78% at 5 years after ECP (Lima et al. ).…”
Section: Surgical Failurementioning
confidence: 99%
“…In the single largest study ( n = 539), after 5 years, the IOP was between 6–21 mmHg in 79% of cases on an average of 1.9 medications (Lima et al. ).…”
Section: Prognosismentioning
confidence: 99%
“…On the contrary, 4 articles described choroidal detachment following ECP at a rate of 1%–5% ( Table 1 ). 5 8 In spite of that, none of these patients were reported to require choroidal drainage, as indicated in our case.…”
Section: Discussionmentioning
confidence: 53%
“…Review of the published results on the incidence of choroidal detachment following ECP. [5][6][7][8] Author (year)…”
Section: Discussionmentioning
confidence: 99%